Rules of civility - Towles, Amor. (New York : Viking, 2011)
A chance encounter with a handsome banker in a jazz bar on New Year's Eve 1938 catapults Katey Kontent into the upper echelons of New York society, where she befriends a shy multi-millionaire, an Upper East Side ne'er-do-well, and a single-minded widow.
Keywords: Upper class -- New York (State) -- New York -- Fiction; Nineteen thirties -- Fiction; Wall Street (New York, N.Y.) -- Fiction; New York (N.Y.) -- Fiction; Psychological fiction